36.6k views
5 votes
Given that f(x) = x^2 + 4x, evaluate f(-2)

User Hynekcer
by
5.0k points

2 Answers

7 votes
Hi there!

To find f(-2), we need to plug in the value x = -2 into the equation.


f( - 2) = ( - 2) {}^(2) + 4 * - 2 = 4 - 8 = - 4
Remember that multiplying a negative by a positive ends up with a positive.

~ Hope this helps you!
5 votes
Hi there!

• f(x) = x² + 4x

• Then,
For finding th' value of f(-2). Substitute " -2 " in place of " x "

f(-2) = (-2)² + 4 × - 2

Exponents first. Accr'ding to P.E.M.D.A.S.

f(-2) = 4 + 4 × - 2

f(-2) = 4 + (-8)

f(-2) = 4 - 8

f(-2) = - 4

Hence, f(-2) = - 4

~ Hope it helps!

User Julien Marrec
by
5.5k points